The Controversy over the Free-Trade Agreement TTIP - Philipp M. Richter; Greta F. Schäffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
A short name is causing a lasting debate: TTIP [ti:t|p]. Ever since the beginning of the negotiations in the summer of 2013, media coverage of the planned Transatlantic Trade and Investment Partnership between the EU and the US has contributed to a critical debate on the topic. In doing so, difficulties have arisen in differentiating factually substantiated arguments from one-sided statements. TTIP is a planned agreement on free trade and investment between the US and the EU, whose details are currently under negotiation. Advocates expect a stimulus on economic growth, new jobs and a strengthening of the transatlantic community of values. Critics point to the lack of transparency in negotiations; they fear an erosion of standards and consumer protection, and see a potential loss of national sovereignty. – – Ein kurzer Name sorgt für eine anhaltende Debatte: TTIP [ti:t|p]. Seit Beginn der Verhandlungen im Sommer 2013 trägt die mediale Berichterstattung über die geplante »Transatlantic Trade and Investment Partnership« zwischen der EU und den USA zur kritischen Auseinandersetzung mit der Thematik bei. Hierbei ergibt sich bisweilen die Schwierigkeit, sachlich fundierte Argumente von einseitigen Stellungnahmen zu differenzieren. Faktisch handelt es sich bei TTIP um ein Freihandels- und Investitionsabkommen, dessen konkrete Ausgestaltung derzeit verhandelt wird. Befürworter erwarten einen Wachstumsimpuls der amerikanischen und europäischen Wirtschaft, neue Arbeitsplätze und eine Stärkung der transatlantischen Wertegemeinschaft. Kritiker weisen demgegenüber auf die Intransparenz des Verhandlungsprozesses hin und fürchten einen Abbau von Standards, eine Beeinträchtigung des Verbraucherschutzes und den Verlust staatlicher Souveränität bei Rechtsprechungen.
Keywords: 330